PSIV-6 Effect of a Direct Fed Microbial Feed Additive on Finishing Beef Cattle Performance and Liver Abscess Rate. (7th May 2021) - Adair, Kelton; Fernando, Samodha; Erickson, Galen E; Bartenslager, Alison; Carlson, Zachary E
Abstract: A feedlot study was conducted comparing the effects of a direct-fed microbial feed additive (DFM) to no feed additive (CON) on performance and liver abscess rates in finishing beef cattle. The study utilized 60 crossbred steers (initial BW 274 kg ± 2.23) individually fed using a Calan gate system. Steers were housed in separate pens by treatment to avoid DFM cross-contamination, with pen (barn of 30 steers) assigned randomly to each treatment. Cattle were fed a diet consisting of 15% corn silage, 36.5% high moisture corn, 24.5% dry rolled corn, 20% modified distillers grains, and 4% supplement for 189 days. The DFM counts were estimated using cell cytometry and was top dressed at a concentration of approximately 81 billion bacterial cells/head/day. The DFM additive used in this study was developed to reduce the abundance of Fusobacterium necrophorum and Streptococcus bovis in the rumen. No effect of treatment on hot carcass weight (HCW), average daily gain (ADG), dry matter intake (DMI), feed efficiency (G:F), or carcass traits (Table 1) were observed. No significant difference in the occurrence of liver abscesses between treatment groups were observed with 4 steers having abscessed livers in the CON group and 3 steers in the DFM group. Additionally, there were no differences in the severity of liver abscesses; all observed liver abscesses received the score of A. The DFM utilized in this study did not significantly affect performance, liver abscess rate, or the severity of liver abscesses in finishing beef cattle.